Effect of Titanium on Microstructure, Texture, and Mechanical Property of As-Extruded Mg—Sn Alloy - Yu, Zhengwen; Zhang, Chang; Tang, Aitao; Li, Caiyu; Liu, Jianguo; Gao, Zhengyuan; Pan, Fusheng (Frontiers in Materials, 2020)
Effect of titanium on microstructure, texture and mechanical properties of as-extruded Mg-Sn alloy has been investigated in the present work. The result reveals that the alloy subjected to the optimized extrusion process shows the extremely refined microstructure with average grain size of 1.7 μm. Meanwhile, the addition of titanium has the obvious effect on intensifying the basal texture where basal slip cannot be easily activated during the tensile testing. As a result, the alloy shows the excellent mechanical properties where yield strength and elongation are 200 MPa and 30.2%, respectively. The enhanced yield strength of the alloy can be attributed to the extremely refined microstructure and intensified basal texture, while the improved elongation of the alloy can be explained as the ultra-fine grained microstructure through reducing the critical resolved shear stress (CRSS) that favors prismatic slip activity to accommodate basal slip.